Customers’ satisfaction of the occupational therapy services in Namibia - Marwa, Thelma; Mitonga, Kabwebwe Honore; Hofnie-//Hoebes, Kathe (International Journal Of Community Medicine And Public Health, 2017)
Background: Patients’ satisfaction is important in healthcare services. It can be an indicator of quality of services in a hospital. The study aims to determine the customers’ satisfaction of the Occupational Therapy Services at Katutura State Hospital in Windhoek. Methods: The research design was a mixed approach - quantitative and qualitative. Questionnaires and interviews were used to collect data. The statistical package for the social sciences software version 23 was used to analyse data. Results: Results of the study showed that occupational therapy patients at Katutura State Hospital are satisfied with the quality of service. However, the service was not superior. Perceived quality mean of the service was 5.51 while the desired quality of service was 9.45. Out of the three dimensions; quality of care, physical environment and occupational therapy services, patients were mostly satisfied with quality of care with the adequacy mean of 1.02 and least satisfied with the physical environment which had an adequacy mean of 0.31. Patients were not satisfied with the cleanliness, ventilation, privacy, lighting, waiting time, consent before treatment and follow up of patients. Conclusions: The study shows that the occupational therapy patients at Katutura State Hospital are slightly satisfied with the services although there are some other factors they are dissatisfied with. The occupational therapy department is recommended to develop consent forms, improve on waiting time and keeping appointments. The physical environment also needs to be improved in order to increase the patients` satisfaction rate.